Molecular spectroscopy and dynamics of intrinsically fluorescent proteins: Coral red (dsRed) and yellow (Citrine) - Heikal, Ahmed A. (The National Academy of Sciences, 2000)
Gene expression of intrinsically fluorescent proteins in biological systems offers new noninvasive windows into cellular function, but optimization of these probes relies on understanding their molecular spectroscopy, dynamics, and structure. Here, the photophysics of red fluorescent protein (dsRed) from discosoma (coral), providing desired longer emission/absorption wavelengths, and an improved yellow fluorescent protein mutant (Citrine) (S65G/V68L/Q69 M/S72A/T203Y) for significant comparison, are characterized by using fluorescence correlation spectroscopy and time-correlated single-photon counting. dsRed fluorescence decays as a single exponential with a 3.65 ± 0.07-ns time constant, indicating a single emitting state/species independent of pH 4.4–9.0, in contrast with Citrine. However, laser excitation drives reversible fluorescence flicker at 10(3)-10(4) Hz between dark and bright states with a constant partition fraction f(1) = 0.42 ± 0.06 and quantum yield of ≈3 × 10(−3). Unlike Citrine (pKa≈5.7), pH-dependent proton binding is negligible (pH 3.9–11) in dsRed. Time-resolved anisotropy of dsRed reveals rapid depolarization (211 ± 6 ps) plus slow rotational motion (53 ± 8 ns), in contrast with a single rotational time (16 ± 2 ns) for Citrine. The molecular dimensions, calculated from rotational and translational diffusion, indicate that dsRed is hydrodynamically 3.8 ± 0.4 times larger than predicted for a monomer, which suggests an oligomer (possibly a tetramer) configuration even at ≈10(−9) M. The fast depolarization is attributed to intraoligomer energy transfer between mobile nonparallel chromophores with the initial anisotropy implying a 24 ± 3° depolarization angle. Large two-photon excitation cross sections (≈100 GM at 990 nm for dsRed and ≈50 GM at 970 nm for Citrine), advantageous for two-photon-fluorescence imaging in cells, are measured.